ENVIRONMENTAL CULTURE AS A COMPONENT OF SUSTAINABLE FUNCTIONING IN THE MILITARY SECURITY SYSTEM - Mammadov, Elnur (Collection of scientific papers «ΛΌГOΣ», 2025)
The intersection of environmental culture and military security has become increasingly significant in the face of modern challenges such as climate change, resource scarcity, and ecological degradation. Environmental culture in the military is not merely a matter of protecting natural resources; it is a strategic imperative that directly impacts the sustainability and operational readiness of armed forces. In an era of complex security threats, the military's ability to operate effectively depends not only on technological advancements and tactical proficiency but also on its capacity to integrate environmental considerations into all aspects of military operations.